(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The study of young people's knowledge of history and ways of learning is relevant because there is currently a subject "History and Social Studies I", where such subjects as economics, politics, social studies, geography and history must be taught at the same time. This is the year when the subject "History I" will be separated from it in the autumn, while the others will continue to remain combined. The idea of ​​teaching a combined subject was presented in 2017 as part of the school reform "School 2030". Understanding the history of technological discovery is important in absolutely every industry. In the past, this task was partially fulfilled by the history subject in the school. This article will analyze the acquisition of historical knowledge in schools. The aim of the research is to find out what secondary school students know about history in the 20th-century context, as well as the ability to see regularities in relation to European and world events. 20th century the middle and the end are chosen because it is a hot topic these days in connection with the war in Europe and the flow of various information / misinformation. In this study, the in-depth interview method was used, when the most active leading experts in the history of the Latvian state – the chairman of the Association of History and Social Science Teachers, the most active members of the association in society, one of whom is also a historian, who is also the author of several history textbooks and a history specialist of the State Education Development Agency – were asked about issues of Latvian history. This study would serve as a basis for further work by surveying both teachers and high school students. One of the main conclusions of the study is that the pupils learn alarmingly little, especially about the 20th century events, especially the last third of the century. The number of hours allocated for this is often made up of reviews, which unfortunately do not look at the issues of technological development at all, when compared to the time before the reform. It should be noted that often the combined subject is taught only by a specialist in one field, who may also be a political scientist or a social science specialist, paying less attention to other subjects accordingly.